Penganalisis Efektifitas Pemasaran Destinasi Wisata Di Jepara: Studi Pada Destinasi Wisata Pantai Bandengan Jepara - Herry Widodo; Sulida Erliyana (Journal Of Business, Finance, and Economics (JBFE), 2023)
This research aims to determine the influence of Promotion Orientation Commitment. Community Participation in Building Tourism Villages. The role of the Government simultaneously and partially in the development of tourist destinations. The independent variable used in this research is Promotion Orientation Commitment. Community participation in developing tourism villages. The Role of Government Administration. The population used in this research was the entire population of Bandengun village. The sample used in this research was 100 respondents using a purposive sampling method. This research uses primary data obtained from distributed questionnaires. ;\The data analysis method used_, is multiple linear regression analysis using SPSS 21. The results of this study show that Promotion Orientation Commitment (X I) has a positive and significant effect on the development of tourist destinations (Y) as evidenced by a sig of 0.000, so there is a significant influence. Community participation in developing tourist villages (X2) has a positive and significant influence on the development of tourist destinations, proven by a sig value of 0.000, meaning there is a significant influence. The role of government (X3) has a positive and significant influence on the development of tourist destinations, proven by a sig value of 0.000, meaning there is significant influence. Commitment to promotional orientation (X1), community participation in developing tourist villages (X2) and the role of government (X3) simultaneously have a positive and significant influence on the development of tourist destinations (Y) as evidenced by the calculated f value of 86,860 > f table of 3.09 with a sig value of 0.000 <0.05. The results of the regression equation are Y = 0.083 + 0.442 X1 + 0.311 X2 + 0.279 X3 + e. The coefficient of determination value is shown by the R Square value of 0.731 or 73.1%, influenced by other variables not examined in this research.